The evolution of copulation frequency and the mechanisms of reproduction in male Anolis lizards. Issue 6 (1st December 2014) - Johnson, Michele A.; Lopez, Maria Veronica; Whittle, Tara K.; Kircher, Bonnie K.; Dill, Alisa K.; Varghese, Divina; Wade, Juli
Abstract: The evolution of many morphological structures is associated with the behavioral context of their use, particularly for structures involved in copulation. Yet, few studies have considered evolutionary relationships among the integrated suite of structures associated with male reproduction. In this study, we examined nine species of lizards in the genus Anolis to determine whether larger copulatory morphologies and higher potential for copulatory muscle performance evolved in association with higher copulation rates. In 10–12 adult males of each species, we measured the size of the hemipenes and related muscles, the seminiferous tubules in the testes, and the renal sex segments in the kidneys, and we assessed the fiber type composition of the muscles associated with copulation. In a series of phylogenetically-informed analyses, we used field behavioral data to determine whether observed rates of copulation were associated with these morphologies.We found that species with larger hemipenes had larger fibers in the RPM (the retractor penis magnus, a muscle that controls hemipenis movement), and that the evolution of larger hemipenes and RPM fibers is associated with the evolution of higher rates of copulatory behavior. However, the sizes of the seminiferous tubules and renal sex segments, and the muscle fiber composition of the RPM, were not associated with copulation rates. Further, body size was not associated with the size of any of the reproductive structures investigated. The results of this study suggest that peripheral morphologies involved in the transfer of ejaculate may be more evolutionarily labile than internal structures involved in ejaculate production.